2022
DOI: 10.3390/ijerph19159653
|View full text |Cite
|
Sign up to set email alerts
|

Are Organizational Interventions Effective in Protecting Healthcare Worker Mental Health during Epidemics/Pandemics? A Systematic Literature Review

Abstract: It is unclear how to effectively protect healthcare workers’ mental health during infectious disease epidemics. Targeting the occupational determinants of stress may hold more promise than individual stress management, which has received more focus. Through a systematic review of the 2000–2021 English- and French-language scientific literature, we evaluated the effectiveness of organizational and psychosocial work environment interventions to protect healthcare workers’ mental health in an epidemic/pandemic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Therefore, whether the increased cardiovascular risk was caused by burnout due to the pandemic remains unclear in the present study. Ensuring that interventions are theoretically designed to address the occupational determinants of stress and that workers are involved in change processes should increase the likelihood of better health outcomes for HCWs during emergencies [ 24 ]. A follow-up and moderated approach are needed to establish the cause–effect relationships between the event, behavior, and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether the increased cardiovascular risk was caused by burnout due to the pandemic remains unclear in the present study. Ensuring that interventions are theoretically designed to address the occupational determinants of stress and that workers are involved in change processes should increase the likelihood of better health outcomes for HCWs during emergencies [ 24 ]. A follow-up and moderated approach are needed to establish the cause–effect relationships between the event, behavior, and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of interventions also varied widely. 21 In another systematic review that extended from 2003 to 2020 and included patients, health workers, and the general public, the researchers found that the prevalence of probable depressive disorder and PTSD in healthcare workers after the 2002-2003 SARS outbreak was 12 and 11%, respectively. 22 In another rapid systematic review researchers explored what health workforce factors were associated with psychological distress in the context of working during an infectious disease outbreak.…”
Section: Psychosocial Support and Mental Healthmentioning
confidence: 99%
“…This project integrated three complementary approaches to gathering knowledge. It included a systematic literature review evaluating the effectiveness of interventions targeting work organization or the psychosocial work environment to protect HCWs' mental health during epidemics [45,46]. It also included an online survey about organizational measures implemented in healthcare establishments to mitigate psychosocial work exposure during the pandemic, as reported by human resources staff.…”
Section: A Health System Already Vulnerablementioning
confidence: 99%